(untitled) - Ohkawa, Kazushi (Tokyo, 1994)
Report on research conducted at the International Development Center of Japan about technology diffusion, productivity employment, and phase shifts in developing economies
Keywords: Technological innovations,Đổi mới công nghệ,Diffusion of innovations,Khuếch tán công nghệ; Japan,Nhật Bản; Japan,Nhật Bản